THE THEFT CASE AT PANAI HILIR POLICE SECTOR VIEWED JURIDICALLY IN RELATION TO ARTICLE 364 OF THE CRIMINAL CODE AND SUPREME COURT REGULATION NO. 2 OF 2012 - Tree One Maret Ritonga; Muhammad Hizbullah (CV. Barokah Publsiher, 2026)
Police Sector from a juridical perspective based on Article 364 of the Indonesian Criminal Code (KUHP) and Supreme Court Regulation Number 2 of 2012 concerning the Adjustment of the Threshold for Minor Offenses and the Amount of Fines in the Criminal Code. The results of the study indicate that the implementation of Supreme Court Regulation Number 2 of 2012 in handling minor theft cases involving zinc at the Panai Hilir Police Sector has not been effective. This ineffectiveness is due to the limited understanding of law enforcement officers, the absence of explicit authority granted to investigators under the Regulation, the lack of technical guidelines at the police level, and a legal culture that remains formalistic. In addition, the provisions of Supreme Court Regulation Number 2 of 2012 normatively regulate the thresholds for minor offenses and the applicable mechanisms.